2005
DOI: 10.1111/j.0142-5463.2005.00265_2.x
|View full text |Cite
|
Sign up to set email alerts
|

L‐Ergothioneine scavenges superoxide and singlet oxygen and suppresses TNF‐α and MMP‐1 expression in UV‐irradiated human dermal fibroblasts

Abstract: Ergothioneine (EGT) is a sulfur‐containing amino acid, and is presumed to function as a natural antioxidant. The purpose of this study was to identify the nature of the antioxidant activity and investigate the effects of EGT on UV‐induced cellular response. In chemical studies, EGT scavenged the superoxide anion radical (•O2–) and singlet oxygen (1O2). In cultured fibroblasts, EGT suppressed TNF‐α upregulation by UVB irradiation. In addition, in fibroblasts exposed to UV‐A, EGT suppressed the expression of mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 23 publications
0
56
0
Order By: Relevance
“…In our study, elevated ROS in UVA exposed cells were substantially inhibited by EGT pretreatment, indicating the free radical scavenging activity and dermato-protective properties of EGT at low concentrations. Under different stress conditions, in vitro studies have shown that EGT is capable of scavenging the various free radicals, such as superoxide, hydroxyl and peroxynitrite [16,22,28], and deactivate the 1 O 2 at a higher rate than GSH [29]. Although in vivo antioxidant properties of EGT not fully established, the accumulation, distribution and scavenging properties of EGT emphasizes its antioxidant property.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, elevated ROS in UVA exposed cells were substantially inhibited by EGT pretreatment, indicating the free radical scavenging activity and dermato-protective properties of EGT at low concentrations. Under different stress conditions, in vitro studies have shown that EGT is capable of scavenging the various free radicals, such as superoxide, hydroxyl and peroxynitrite [16,22,28], and deactivate the 1 O 2 at a higher rate than GSH [29]. Although in vivo antioxidant properties of EGT not fully established, the accumulation, distribution and scavenging properties of EGT emphasizes its antioxidant property.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, EGT treatment reported to scavenge the 1 O 2 radicals, and suppress the expression of matrix metalloproteinase-1 in UVA-irradiated dermal fibroblasts [22].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Ergothioneine was first identified as an antioxidant in cell-free experiments. It inhibits formation of hydroxyl radical (Motohashi and Mori, 1986), and superoxide anions (Cargnoni et al, 1995), singlet oxygen at ASPET Journals on May 11, 2018 jpet.aspetjournals.org production (Obayashi et al, 2005), lipid peroxidation (Deiana et al, 2004), and peroxynitrite oxidative damage (Aruoma et al, 1997). As opposed to other naturally occurring thiols (e.g., glutathione, N-acetylcysteine), ergothioneine is present in aqueous solutions predominantly as a thione rather than a tautomeric thiol structure.…”
Section: Introductionmentioning
confidence: 99%
“…In cultured fibroblasts, ergothioneine suppresses the UVBinduced upregulation of tumor necrosis factor-a. In addition, ergothioneine suppresses the expression of MMP-1 protein in fibroblasts exposed to UVA by quenching 1 O 2 (Obayashi et al 2005). Zn(II)-glycine, a coordinated compound of Zn 2+ and glycine, which is a cellmembrane permeable inducer of metallothionein and GSH, protects against UVBinduced cell damage and also suppresses IL-1a secretion and prostaglandin E 2 synthesis in human keratinocytes (Ochiai et al 2008).…”
Section: Natural Substancesmentioning
confidence: 99%